Digital ICT in Education Deconstructing Myths and Realities - Ramadas, V. (JOURNAL OF INDIAN EDUCATION, 2018)
Myths play a powerful and significant role in curriculum and educational practices. They generate a range of responses from the teachers, teacher educators and educational researchers. Some of us seek to challenge and transform persistent myths associated with the curriculum; others may focus on interrogating myths understood as popular misconceptions in teaching and learning; still others consider myths as powerful narratives and stories that evoke timely or timeless messages about current educational practices. Myths can be productive learning tools, as they create and sometimes recreate narratives that are neatly wrapped around culturally based messages and truths. However, many of them have a darker side; some are irrational and others are beguilingly but ultimately dangerously attractive. Deconstructing the mythical thinking about digital ICT is highly significant for promoting critical thinking, constructing sound knowledge and preventing ignorance-based mistakes in educational practices. This paper attempts to create awareness among the educators and researchers about how our beliefs and views on ICT in education are built; invites them to critically consider to what extent these beliefs and views have rational and evidence-based grounding; and emphasises the need to identify and challenge the myths of ICT in education that prevent productive and evidence-based approaches to current educational problems.